Holy grounds : the surprising connection between coffee and faith - from dancing goats to Satan's drink - Schenck, Tim (Fortress Press, 2019)
If you're religious about your coffee, you're in holy company. If you like your coffee with a bit of inspiration, a hint of humor, and a dose of insight, you'll enjoy pouring a mug full of java and curling up with Holy Grounds. Popular author and avid coffee drinker Tim Schenck brews just the right blend of the personal and historical as he explores the sometimes amusing and often profound intersection between faith and coffee. From the coffee bean's discovery by ninth-century Ethiopian Muslims to being condemned as "Satan's drink" by medieval Christians, to becoming an integral part of Passover in America, coffee has fueled prayer and shaped religious culture for generations. In Holy Grounds, Schenck explores the relationship between coffee and religion, moving from faith-based legends that have become entwined with the history of coffee to personal narrative. He takes readers on a journey through coffee farms in Central America, a pilgrimage to Seattle, coffeehouses in Rome, and a monastic community in Pennsylvania. Along the way, he examines the power of ritual, mocks bad church coffee, introduces readers to the patron saint of coffee, wonders about ethical considerations for today's faith-based coffee lovers, and explores lessons people of faith should learn from coffeehouse culture about building healthy, authentic community